2014
DOI: 10.1038/nutd.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acid profiles are associated with insulin, C-peptide and adiponectin levels in type 2 diabetic patients

Abstract: Objectives:Plasma-free amino acid (PFAA) profiles have been associated with a future risk of developing diabetes or cardiovascular disease in nondiabetic subjects. These PFAA alterations might predominantly result from the metabolic shift caused by insulin resistance and visceral fat deposition. The variety of PFAA profiles within diabetic subjects is not well researched. In this study, we focused on type 2 diabetic subjects and examined the association between PFAA profiles and insulin- and glucose-related va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 31 publications
8
71
1
1
Order By: Relevance
“…In similarity to our study, higher plasma amino acid levels have repeatedly been reported to associate with insulin resistance (Newgard et al 2009;Tai et al 2010;Wurtz et al 2012a;Nakamura et al 2014;Seibert et al 2015;Pedersen et al 2016). To this end, plasma amino acid levels, in particular of the branched chain amino acids valine, leucine, and isoleucine, aromatic amino acids tyrosine and phenylalanine, and alanine, are predictive of development of type 2 diabetes even several years before its onset (Wang et al 2011;Wurtz et al 2012bWurtz et al , 2013Yamakado et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In similarity to our study, higher plasma amino acid levels have repeatedly been reported to associate with insulin resistance (Newgard et al 2009;Tai et al 2010;Wurtz et al 2012a;Nakamura et al 2014;Seibert et al 2015;Pedersen et al 2016). To this end, plasma amino acid levels, in particular of the branched chain amino acids valine, leucine, and isoleucine, aromatic amino acids tyrosine and phenylalanine, and alanine, are predictive of development of type 2 diabetes even several years before its onset (Wang et al 2011;Wurtz et al 2012bWurtz et al , 2013Yamakado et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The only AA, which change with T2DM evolution was found characteristic only for OB group was lysine. Based on literature data T2DM has minor effect on lysine metabolism , however it was found to be correlated with plasma glucose level . Also in our study, the change of lysine is minor, and observed only in obese subjects.…”
Section: Resultssupporting
confidence: 65%
“…Our previous study also found that sex is a more influential factor for PFAA profiles than age or BMI (Yamamoto et al, 2015). In addition, reports have indicated that PFAA levels are strongly correlated with visceral fat area and insulin‐related parameters but not with subcutaneous fat area (Nakamura et al, 2014; Yamakado et al, 2012). Furthermore, the ingestion of a low‐protein diet leads to decreased PFAA levels (Fujita et al, 1978).…”
Section: Discussionmentioning
confidence: 99%